Immunohistochemical mapping of pro-opiomelanocortin- and pro-dynorphin-derived peptides in the alpaca (Lama pacos) diencephalon - Manso B. (2014)
The authors thank Professor Gérard Tramu (University of Bordeaux I, France) for kindly providing the first antisera and N. Skinner (University of Salamanca, Spain) for stylistic revision of the English text. This work has been supported by the Ministerio de Educación y Ciencia (BFU2005-02241/BFI), Spain and the Ministerio de Ciencia e Innovación (BFU2008-03369/BFI), Spain and by the CONCYTEC: PROCYT project 2006, Peru.